2010
DOI: 10.1002/pat.1875
|View full text |Cite
|
Sign up to set email alerts
|

The use of functionalized nanoparticles as non‐specific compatibilizers for polymer blends

Abstract: The ability to form blends of polymers offers the opportunity of creating a new class of materials with enhanced properties. In addition to the polymer components, recent advances in nanoengineering have resulted in the development of nanosized inorganic particles that can be used to improve the properties of the blend, such as the flammability and the mechanical properties. While traditional methods using copolymer compatibilizers have been used to strengthen polymer blends, here, we show that the inorganic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The slight increase in the tensile strength in PDAP/EPDM-20/100 is probably due to the good interfacial interactions between fillers by introducing certain amounts of stronger polar molecules of PDAP and appropriate vulcanizing rate with TAIC/DCP. 24 26 Similar trends of decreasing effects were found for the elongation at break for silicone/EPDM insulations due to the dispersion of the secondary matrix from the continuous phase to the dispersed phase. 27 29 Meanwhile, the PDAP/EPDM blends retained higher values of elongations, hinting that PDAP might show better compatibility with EPDM due to its higher polarity and the better interfaces between them.…”
Section: Resultssupporting
confidence: 60%
“…The slight increase in the tensile strength in PDAP/EPDM-20/100 is probably due to the good interfacial interactions between fillers by introducing certain amounts of stronger polar molecules of PDAP and appropriate vulcanizing rate with TAIC/DCP. 24 26 Similar trends of decreasing effects were found for the elongation at break for silicone/EPDM insulations due to the dispersion of the secondary matrix from the continuous phase to the dispersed phase. 27 29 Meanwhile, the PDAP/EPDM blends retained higher values of elongations, hinting that PDAP might show better compatibility with EPDM due to its higher polarity and the better interfaces between them.…”
Section: Resultssupporting
confidence: 60%
“…Zhang et al [158] made films based on 50/50 PS/PMMA (prepared by solution in toluene) with 5 vol% of three different nanoparticles: Cloisite ® 6A (that is an organically modified montmorillonite), tungsten disulfide nanotubes and tungsten disulfide multi-layered "onion" shaped particles. They showed that W 2 S onion shaped nanoparticles do not affect the phase segregation morphology, whereas the other two do.…”
Section: Influence Of the Shapementioning
confidence: 99%
“…In comparison with nanotubes and spherical nanofillers such as nanosilica, layered nanosilicate with much larger aspect ratio has been verified to be more efficient in compatibilizing the LCST blends and reducing the interfacial tension of polymers by providing large amounts of in situ grafts between two components at the interface. Moreover, the authors found that the thermodynamic effect of nanoclay (NC) on an immiscible polymer blend was an equilibrium phenomenon whereupon the biphasic morphology was stabilized after long periods of annealing . Likewise, Bousmina's group reported that nanoclay can alter the phase behavior of LCST blends both thermodynamically and kinetically and the phase transition mechanism changes from spinodal decomposition to nucleation and growth by the incorporation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%